2014
DOI: 10.20885/jaai.vol18.iss2.art3
|View full text |Cite
|
Sign up to set email alerts
|

Theory of planned behavior dan readiness for change dalam memprediksi niat implementasi peraturan pemerintah nomor 71 tahun 2010

Abstract: Theory of Planned Behavior (TPB) has been widely applied in various fields of behavioral research, to address behaviors that are not under the full control of the individual. This research aimed to analyzing the effect of: 1) attitude toward the behavior; 2) subjective norm; 3) perceived behavioral control; and 4) readiness for changeon the intention to implementing the Government Regulation No.71 Year 2010 concerning the accrual-based governmental accountingstandard. This research used a quantitative approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
(19 reference statements)
0
7
0
2
Order By: Relevance
“…Kepatuhan organisasi pemerintah untuk menerapkan SAP berbasis akrual merupakan amanat PP 71 tahun 2010 sehingga memiliki konsekuensi untuk wajib dilaksanakan dan bersifat memaksa karena memang demikian sejatinya sifat peraturan perundang-undangan (Afdalia, Pontoh, dan Kartini, 2014;Suhendro dkk., 2015). Oleh karena itu, Pemerintah Provinsi Hastinapura sebagaimana pemerintah daerah lain di Indonesia, berusaha mematuhi peraturan perundang-undangan yang berlaku dengan mengimplementasikan akuntansi berbasis akrual.…”
Section: Hasil Dan Pembahasanunclassified
“…Kepatuhan organisasi pemerintah untuk menerapkan SAP berbasis akrual merupakan amanat PP 71 tahun 2010 sehingga memiliki konsekuensi untuk wajib dilaksanakan dan bersifat memaksa karena memang demikian sejatinya sifat peraturan perundang-undangan (Afdalia, Pontoh, dan Kartini, 2014;Suhendro dkk., 2015). Oleh karena itu, Pemerintah Provinsi Hastinapura sebagaimana pemerintah daerah lain di Indonesia, berusaha mematuhi peraturan perundang-undangan yang berlaku dengan mengimplementasikan akuntansi berbasis akrual.…”
Section: Hasil Dan Pembahasanunclassified
“…Meanwhile, compliance intention in the organisational context may be defined as a cognitive representation of one's readiness in the form of impetuses that consciously emerge to believe, accept and act on all organisational policies, provisions and rules voluntarily (Darley et al, 2001). Several prior studies have also found compliance intention as a predictor of work behaviour (Afdalia et al, 2014;Hartoni & Riana, 2015;Yami, 2015).…”
Section: Intention As a Work Culture Determinant At The Ministry Of R...mentioning
confidence: 93%
“…In research by Sarrah et al (2016), it was found that higher perceptions of control and ability taxpayers will encourage their compliance intentions. Afdalia et al (2014) have proven that compliance intentions can predict the implementation of Governmental Regulation No. 71 of 2010 on the Accrual Based Government Accounting Standards.…”
Section: Introductionmentioning
confidence: 99%
“…Theory of Planned Behavior (TPB) refers to the theory which states that behavior is a function of salient information or beliefs about the behavior. TPB explains that human actions are directed by three kinds of beliefs, namely (a) behavioral beliefs, namely beliefs about the possibility of behavior, (b) normative beliefs, namely beliefs about normative expectations from others and the motivation to agree to these expectations, (c) beliefs control, namely beliefs about the existence of factors that will facilitate or hinder behavioral performance and the perceived strength of these factors (Afdalia et al, 2014).…”
Section: Planned Behavior Theorymentioning
confidence: 99%